Effects of early pulmonary rehabilitation exercise on the lung function and indicators of arterial blood gas analysis in patients with severe chronic obstructive pulmonary disease (早期分阶段肺康复锻炼对重症慢性阻塞性肺疾病患者肺功能及血气指标的影响) - XU Nannan (徐楠楠); HONG Hanhan (洪涵涵) (中西医结合护理)
Objective To investigate the effect of early lung rehabilitation exercise and nursing interventions on the lung function and indicators of arterial blood gas analysis in patients with severe chronic obstructive pulmonary disease (COPD). Methods Seventy patients with severe COPD undergoing pulmonary rehabilitation were selected as the study objectis, and were randomly divided into the observation group and the control group, with 35 patients in each group. The control group received routine nursing and pulmonary rehabilitation, and the observation group received early lung rehabilitation exercise on the basis of control group. Indicators of arterial blood gas analysis and lung function were measured and compared between two groups before intervention and 3 months after intervention. Results PaO2 increased in both groups and was significantly higher after 3 months compared with that before intervention, and PaO2 in the observation group was higher than that in the control group (P＜0. 05). PaCO2 decreased in both groups was lower after 3 months, and PaCO2 in the observation group was lower than that in the control group (P＜0. 05). Patients in both groups were observed with higher FEV1/FVC and PEF after 3 months, and FEV1/FVC and PEF of pateints in the observation group were higher than those of patients in the control group(P＜0. 05). Conclusion The early pulmonary rehabilitation exercise can improve the outcomes of arterial blood gas analysis and recovery of lung function of patients with severe chronic obstructive pulmonary disease. (目的 探讨早期分阶段肺康复锻炼对重症慢性阻塞性肺疾病(COPD)患者肺功能及血气指标的改善作用。方法 选取2022年6月—2023年3月医院收治的实施肺康复的重症COPD患者70例为研究对象, 采用随机数字表法分成观察组与对照组, 各35例。对照组实施常规护理和肺康复锻炼, 观察组在对照组基础上实施早期分阶段肺康复锻炼。比较两组患者干预前及干预3个月后的血气分析指标、肺功能变化。结果 干预3个月后, 两组动脉氧分压(PaO2)高于干预前, 且观察组PaO2高于对照组, 差异有统计学意义(P＜0. 01); 两组动脉二氧化碳分压(PaCO2)低于干预前, 且观察组PaCO2低于对照组, 差异有统计学意义(P＜0. 01)。两组1s用力呼气容积(FEV1)与用力肺活量(FVC)比值(FEV1/FVC)、呼气流量峰值(PEF)均高于干预前, 且观察组高于对照组, 差异有统计学意义(P＜0. 01)。结论 早期分阶段肺康复锻炼能够改善COPD患者血气分析指标, 改善患者肺功能。)